2015 IEEE 4th Portuguese Meeting on Bioengineering (ENBENG) 2015
DOI: 10.1109/enbeng.2015.7088834
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stresses in drilled composite materials

Abstract: PrefaceThis book contains the abstracts and full papers presented at the IEEE 4th Portuguese Meeting on Bioengineering (ENBENG) organized by the IEEE Engineering in Medicine & Biology Society (EMBS) Chapter of the IEEE Portugal Section that was held in "Atmosfera m", in the city of Porto, between 26th and 28th, February of 2015.The Portuguese Meeting on Bioengineering is one of most important meetings organized in Portugal related with the Bioengineering field and where students and researchers present and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The hole generation during the drilling process was simulated by the element deletion that occurs when the plastic strain of an element reached the limit. 8 LS-DYNA provides specific types of contact and several criteria for removing elements during a numerical simulation. A surface-to-surface contact analysis was established between drill bit and biomechanical block.…”
Section: Element Removal and Contact Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hole generation during the drilling process was simulated by the element deletion that occurs when the plastic strain of an element reached the limit. 8 LS-DYNA provides specific types of contact and several criteria for removing elements during a numerical simulation. A surface-to-surface contact analysis was established between drill bit and biomechanical block.…”
Section: Element Removal and Contact Interactionsmentioning
confidence: 99%
“…One of these problems is the cut effort achieved during the process and it directly related with the drilling parameters. [8][9][10] Usually, the drilling procedures are performed using the conventional drill bit through hand drills, which means that the feedrate is manually controlled by the surgeon. Thus, the cutting effort sensed by the surgeon is subjective and depends on the tool feed-rate, the bone quality and the type of the cut tool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion was verified by comparison with the surface profile after the experiment. Fernandes et al [10] built a three-dimensional dynamic model of the composite to simulate the drilling process. The results showed that the composites were less stressed and strained with the higher feed rate.…”
Section: Introductionmentioning
confidence: 99%
“…Based on temperature measurements, several studies have been carried out to assess various parameters that influence surgical drilling into bone. 1,12,13,[32][33][34][35][36][37][38][39] However, the complexity of the process and the extensive number of variables involved complicates the statement of concluding remarks. Experimental models coupled to other methodologies, such as computational models, has been a common practice in this type of analysis.…”
Section: Introductionmentioning
confidence: 99%